New Mediterranean Biodiversity Records (March 2016) - P. K. KARACHLE; A. ANGELIDIS; G. APOSTOLOPOULOS; D. AYAS; M. BALLESTEROS; C. BONNICI; M. M. BRODERSEN; L. CASTRIOTA; N. CHALARI; J. M. COTTALORDA; F. CROCETTA; A. DEIDUN; et al. (Mediterranean Marine Science, 2016)
In this Collective Article on “New Mediterranean Biodiversity Records”, we present additional records of species found in the Mediterranean Sea. These records refer to eight different countries throughout the northern part of the basin, and include 28 species, belonging to five phyla. The findings per country include the following species: Spain: Callinectes sapidus and Chelidonura fulvipunctata; Monaco: Aplysia dactylomela; Italy: Charybdis (Charybdis) feriata, Carcharodon carcharias, Seriola fasciata, and Siganus rivulatus; Malta: Pomacanthus asfur; Croatia: Lagocephalus sceleratus and Pomadasys incisus; Montenegro: Lagocephalus sceleratus; Greece: Amathia (Zoobotryon) verticillata, Atys cf. macandrewii, Cerithium scabridum, Chama pacifica, Dendostrea cf. folium, Ergalatax junionae, Septifer cumingii, Syphonota geographica, Syrnola fasciata, Oxyurichthys petersi, Scarus ghobban, Scorpaena maderensis, Solea aegyptiaca and Upeneus pori; Turkey: Lobotes surinamensis, Ruvettus pretiosus and Ophiocten abyssicolum. In the current article, the presence of Taractes rubescens (Jordan & Evermann, 1887) is recorded for the first time in the Mediterranean from Italy. The great contribution of citizen scientists in monitoring biodiversity records is reflected herein, as 10% of the authors are citizen scientists, and contributed 37.5% of the new findings.